Efektivitas Model Pembelajaran Examples Non Examples dengan Media Geogebra terhadap Kemampuan Pemahaman Konsep Matematika Siswa - Kelvin Demanda; Yulia Romadiastri; Dinni Rahma Oktaviani (Jurnal Ilmiah Pendidikan Matematika Al Qalasadi, 2024)
This research aims to analyze the effectiveness of students' conceptual understanding abilities at SMPN 16 Semarang in spatial construction material by utilizing the example non-example learning model with GeoGebra media. This research uses an experimental design with a posttest-only control group and is a form of quantitative research. Class VIIIH was used as the experimental class, and class VIIIG was used as the control class. Samples were obtained using a cluster random sampling approach. Tests and documentation are used in research data collection procedures. The results showed that the average post-test score for experimental class students was while the average post-test score for control class students was From the t-test calculations, the values obtained are and with a sig value. 0.05. Students in the experimental class showed a better level of understanding of mathematical concepts than students in the control group; this can be seen from the findings, which show that tcount > ttable. Therefore, it can be concluded that the Example Non-example model, which utilizes geogebra media increases students' conceptual understanding of spatial construction material.